2000
DOI: 10.1046/j.1365-2486.2000.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2 partial pressure controls the calcification rate of a coral community

Abstract: Summary Previous studies have demonstrated that coral and algal calcification is tightly regulated by the calcium carbonate saturation state of seawater. This parameter is likely to decrease in response to the increase of dissolved CO2 resulting from the global increase of the partial pressure of atmospheric CO2. We have investigated the response of a coral reef community dominated by scleractinian corals, but also including other calcifying organisms such as calcareous algae, crustaceans, gastropods and echin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
131
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(144 citation statements)
references
References 25 publications
8
131
1
4
Order By: Relevance
“…Besides the amount of photons, also other factors may play a role in determining coral growth rate. Factors known to be limiting for the growth of stony corals include water flow (Lesser et al, 1994, Schutter et al, 2011, aragonite saturation state (Gattuso et al, 1998;Leclercq et al, 2000;Schneider & Erez, 2006) and its associated components (Marubini et al, 2008), the availability of essential trace metals such as copper and zinc (Ferrier-Pagès (Jokiel & Coles, 1990;Marshall & Clode, 2004), competition (Rinkevich & Loya, 1985;Tanner, 1995) and sedimentation (Rogers, 1990 , based on data Schutter et al (2008)), suggests that one or more factors were limiting or inhibiting in the current study. However, despite our efforts (see Table 4), the factor(s) limiting or inhibiting coral growth in this study could not be conclusively determined.…”
mentioning
confidence: 60%
“…Besides the amount of photons, also other factors may play a role in determining coral growth rate. Factors known to be limiting for the growth of stony corals include water flow (Lesser et al, 1994, Schutter et al, 2011, aragonite saturation state (Gattuso et al, 1998;Leclercq et al, 2000;Schneider & Erez, 2006) and its associated components (Marubini et al, 2008), the availability of essential trace metals such as copper and zinc (Ferrier-Pagès (Jokiel & Coles, 1990;Marshall & Clode, 2004), competition (Rinkevich & Loya, 1985;Tanner, 1995) and sedimentation (Rogers, 1990 , based on data Schutter et al (2008)), suggests that one or more factors were limiting or inhibiting in the current study. However, despite our efforts (see Table 4), the factor(s) limiting or inhibiting coral growth in this study could not be conclusively determined.…”
mentioning
confidence: 60%
“…Coral calcification probably depends on coral conditions such as size, mode, health and species. In addition, Gattuso et al (1998) Leclercq et al (2000) also pointed out that the coral samples used by Gattuso et al (1998) showed less response to changes in CO 2 system and provided a plateau in calcification rate when W reached over 3.90.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, the role and function of calcareous ecosystems and communities may be altered as a result of future changing environmental conditions Kleypas et al, 1999Kleypas et al, , 2001Riebesell et al, 2000;Langdon et al, 2000;Mackenzie et al, 2000;Leclercq et al, 2000Leclercq et al, , 2002.…”
Section: The Inorganic Carbon Cycle In the Global Oceanmentioning
confidence: 99%